A qualitative study to explore strategies to improve the Road to Health Application for maternal and child health outcomes in South Africa - Dietrich, Janan Janine; Tsotetsi, Lerato; Dubazane, Thenjiwe; Tshabalala, Gugulethu; Maimela, Boitumelo; Weiss, Martin; Mulaudzi, Mamakiri (Frontiers in Digital Health, 2023)
Background: The Road to Health Application (RTHA) is a digitalized version of the Department of Health’s ( DoH) Road to Health book, a printed booklet given to mothers at the birth of each baby. The RTHA provides guidelines for maternal and child health outcomes specifically to create a database of children and caregivers in South Africa and offers guidelines on how to raise a healthy child. This paper explored potential barriers to using the RTHA based on user experiences. Methods: Using a qualitative design, we conducted 50 serial interviews (two separate interviews, one month apart). Through convenience, sampling eligible participants were 18 years+ women who were pregnant and/or had a child under the age of 5 years. Participants included 25 existing users and 25 new users of the RTHA, who owned android smart phones at enrolment. Existing users were recruited telephonically through the DoH's database and new users were approached at the antenatal care unit and wellness-baby clinic at the Chris Hani Baragwaneth Academic Hospital. Upon enrolment, participants completed a brief socio-demographics survey and thereafter had a baseline interview followed by a telephonic interview one month later. A semi-structured interview guide was used to explore barriers, enablers and usability of the RTHA. Using thematic data analysis we identified barriers to use of the RTHA. Results: A third (33%) of all participants reported IsiZulu as their main language of communication and 6% . Although the RTHA was reported as an essential addition to the RTHA multiple barriers were cited by the participants these included the app being available in only English and IsiZulu, data costs, lack of access to smart phones and app functionalities. The usefulness of the RTHA was cited to be the accessibility of important information regarding pre and post-natal childcare. Conclusion This study gives insight to the barriers from the end-user perspective, and offers guidance on how to improve the RTHA to be more user-friendly which could increase the usability amongst mothers. It further emphasizes the need to consider the challenges experienced by users in South Africa when developing future mobile health interventions to increase uptake.